Establishment of a dual-wavelength spectrophotometric method for analysing and detecting carbapenemase-producing Enterobacteriaceae. Issue 1 (December 2018) - Takeuchi, Dan; Akeda, Yukihiro; Sugawara, Yo; Sakamoto, Noriko; Yamamoto, Norihisa; Shanmugakani, Rathina; Ishihara, Takuma; Shintani, Ayumi; Tomono, Kazunori; Hamada, Shigeyuki
Abstract The spread of carbapenemase-producingEnterobacteriaceae (CPE) is an increasing global public health concern. The development of simple and reliable methods for CPE detection is required in the clinical setting. This study aimed to establish a dual-wavelength measurement method using an ultraviolet–visible spectrophotometer to rapidly quantify imipenem hydrolysis in bacterial cell suspensions. The hydrolytic activities of 148 strains including various CPE strains (Escherichia coli, Klebsiella pneumoniae, Enterobacter cloacae, andEnterobacter aerogenes containing thebla IMP, bla KPC, bla NDM, bla OXA, andbla VIM genes) were measured and analysed. A cut-off value was obtained for differentiation between CPE and non-CPE strains, and the method had high sensitivity (100%) and specificity (100%) within 60 min. Our system has potential clinical applications in detecting CPE.